Analysis of Waste Energy Utilization in Ballast Load at Suka Sama Micro Hydro Power Plant - Purba, Hengki; Hutajulu, Olnes Yosefa; Sinuraya, Arwadi; Nababan, Puji Mory (Jambura Journal of Electrical and Electronics Engineering, 2024)
The electrical power generated by a Micro Hydropower Plant (PLTMH) should be fully utilized without any wastage. The PLTMH Suka Sama, equipped with an Electronic Load Controller (ELC), diverts unused electrical power to a ballast load. This action is necessary to maintain system frequency stability in the event of excess power during a drop in demand. The utilization of energy from PLTMH Suka Sama can be improved by using the electrical power diverted to the ballast load to process sugarcane juice into palm sugar using a vacuum evaporator. The potential energy wasted to the ballast load will be calculated based on the comparison data of the power used by the PLTMH and the power wasted during peak and low demand periods over 9 days. The study results show that the power diverted to the ballast load ranges from 2,000 W to over 3,000 W for 4-7 hours per day. This research indicates that the wasted electrical energy can be utilized to produce palm sugar using a vacuum evaporator with a capacity of 2,000 W for 4-5 hours. The wasted energy, if utilized, can produce 2.5 kg to 3.5 kg of palm sugar.